Rural Savings: Their Magnitude, Determinants, and Mobilisation (The Pakistan Development Review, 1995)
The general view about the rural population in Pakistan is that a vast majority of it has a deplorably low standard of living. The incomes of most of the rural people are so low that one wonders how they manage to survive. Studies on poverty in the country show that the incidence and the intensity of poverty in the villages is much higher than in the towns. Yet the available data about rural incomes and family budgets show that the average propensity of the rural households to save is much higher than the national average. Several questions need to be answered in this regard. Are the data about rural incomes and expenditures reliable? Are the findings a consistent feature over time or only a temporary phenomenon for a year or so? Do only larger farmers save or do the smaller peasants and non-farm rural people also manage to save? Is this finding unique only to our rural populace or is there evidence of similar findings from elsewhere? What is the possible rationale for this unusual saving behaviour? What is the magnitude of rural savings and what could be their role in rural development? Finally, how could these savings be encouraged and mobilised? This paper aims at exploring and answering these questions with the help of whatever data are available. Apart from the Introduction, the paper is divided into five sections. In the first section, we present evidence of high rates of rural savings in Pakistan and some other countries. Section 2 discusses the rationale of this savings behaviour and the determinants of rural savings. In Section 3, we examine the magnitude of rural savings and their possible role in rural development. Section 4 deals with the problem of mobilisation of rural savings. The final section sums up the discussion.